Study of Shading Photovoltaic Module and Fabrication of Solar Data Logger - Shrestha, Bipin; Thapa Magar, Biraj; Chaulagain, Manoj; Awal, Prashant; Gautam, Rupesh; Gwachha, Rakesh (KEC Journal of Science and Engineering, 2026)
Solar photovoltaic (PV) systems are essential for renewable energy production, yet their performance is greatly influenced by shading. The performance of photovoltaic (PV) modules is highly influenced by environmental conditions, with shading being one of the most critical factors causing significant power losses. To investigate this effect, nine different shading strategies were designed based on real-case scenarios commonly encountered in rooftop and field installations, such as partial obstruction by buildings, trees, and nearby structures. This research examines the influence of shading on photovoltaic systems through MATLAB/Simulink simulations and practical experiments. A solar data logger was created to track essential performance metrics, such as voltage, current, temperature, and irradiance. The research confirms the issue of power loss in PV modules due to shading, which results in decreased energy production and efficiency. The main objective is to investigate the impact of various shading strategies, assess their effect on the I-V and P-V characteristics of PV modules, and fabricate a solar data logger system. This system records and analyses real-time data to facilitate performance evaluation and predictive maintenance of PV modules. The findings indicate that shading significantly reduces the output of PV modules, with some shading patterns causing power losses of up to 100%. The hardware results closely match the simulation, confirming the accuracy of the analysis. Additionally, the fabricated solar data logger effectively captures essential PV parameters, providing a reliable tool for long-term system monitoring. This study highlights the impact of shading on PV modules and emphasizes the role of real-time data logging in performance evaluation and predictive maintenance.